The value harmonization mechanism of the industry development programs - Леонова, Світлана Миколаївна (Eastern-European Journal of Enterprise Technologies, 2013)
The article focuses on value-based management applied to the state development program. Program implementation remains inefficient due to imperfect value harmonization instruments. Common methods of balancing of the participant’s interests (like corporate rates) cannot be used state program management. Relevance of the article is provided by necessity of using models and methods of harmonization of stakeholder interests in the state development programs. It describes an evaluation tool of program participant’s interests. Discounted profitability index and minimum return on assets criteria were used as criteria of projects value balancing in the program. It is demonstrated two methods of taking into account the time value of money applying to the project evaluation criteria. The designed model for harmonization the stakeholder’s interests enables to determine the boundary conditions which require application of support measures to the project in order to balance its value. The research results can be applied to the management of state industry development programs